Analisis Balance Scorecard Pada Cafe Solata di Palopo Pada Masa Pandemi Covid -19 - Rian Maming; Ainul Fahmi (Program Pascasarjana STIE Amkop Makassar, 2022)
Abstract This research is to measure and assess the company's performance in need of an integrated and comprehensive performance measurement method consisting of financial and non-financial aspects. This type of research is a qualitative analysis. In this study, the sample used is the 2018-2020 financial report, the balanced scorecard measurement method with 4 aspects, namely financial aspects, customer aspects, internal business aspects, and learning and growth aspects. Data analysis used in this study consisted of financial and non-financial data. Where the results of the research are based on the results of research from a financial perspective, customer perspective, Internal Business Perspective and learning and growth perspective as seen from cafe sorata sales growth using financial performance benchmarks such as sales growth because these benchmarks are generally used in companies to find out how much increased sales growth. From 2018 to 2020 From the results of cafe solata for the last 3 years it can be seen that cafe solata is able to run the company's wheels well. At cafe sonata, innovation is carried out, where the innovation is in the form of adding a list of food and beverage menus in accordance with consumer desires and the progress of the times, most consumers like modern or contemporary food and drinks so that they invite consumers to come and visit cafe solata. Keywords: financial aspects, non-financial aspects, COVID-19